KINERJA DISDUKCAPIL KABUPATEN BULELENG DALAM PELAYANAN MELALUI WEB LAYONSARIKECAPIL.BULELENG KAB.GO.ID DI MASA PANDEMI COVID-19 BERBASIS DIGITAL GOVERNMENT - Rastiti, Luh Eki; Wismayanti, Kadek Wiwin Dwi; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2023)
The COVID-19 pandemic that entered Indonesia in early 2020 became the starting point for the intensification of digital government-based services. Layonsari kecapil is one of the innovations made since mid 2020 by the Population and Civil Registration Office of Buleleng Regency and has been implemented until now, but in the service process on this website it needs to be reviewed with a performance assessment because there are still some problems. This type of research is descriptive qualitative. The results of the study show that the performance of the Population and Civil Registration Office of Buleleng Regency is quite good. Then based on the concept of digital government, there are several indicators that are still less than optimal, namely electronic participation/digital inclusion, cyber security, digital government promotion and for indicators of network readiness, management optimization, online services/applications, national portal/homepage, head of information and data disclosure. government is good enough. Key word : Performance, Layonsari kecapil, Digital Government